2023
DOI: 10.3233/jad-220698
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Role of Astrocyte-Derived Exosomes and Their Contents in the Process of Alzheimer’s Disease

Abstract: Millions of patients worldwide are affected by Alzheimer’s disease (AD), and the number of patients with AD is increasing. However, current treatment can only improve symptoms but cannot cure the disease. Astrocytes, glial cells in the central nervous system, play important roles in support, nutrition, protection, and information transmission in the nervous system. Pathological changes in astrocytes are closely associated with the development and progression of AD. As carriers for material and information exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Next, we determined the cell type that secretes CD9(+) sEVs containing ASM and Aβ1-42 in the 5xFAD brain. While neurons are known to be the major producers of Aβ in the brain, previous studies, including our own work, have shown that astrocyte-derived EVs carry a higher amount of Aβ compared to neuron-derived EVs [ 12 , 34 , 35 ]. In order to investigate whether the cellular origin of Aβ-associated sEVs is sex-specific, ExoView analysis was conducted using fluorescent antibodies specific to glial fibrillary acidic protein (GFAP), which is a marker for astrocytes, and L1 cell adhesion molecule (L1CAM1), which is a marker for neurons.…”
Section: Resultsmentioning
confidence: 91%
“…Next, we determined the cell type that secretes CD9(+) sEVs containing ASM and Aβ1-42 in the 5xFAD brain. While neurons are known to be the major producers of Aβ in the brain, previous studies, including our own work, have shown that astrocyte-derived EVs carry a higher amount of Aβ compared to neuron-derived EVs [ 12 , 34 , 35 ]. In order to investigate whether the cellular origin of Aβ-associated sEVs is sex-specific, ExoView analysis was conducted using fluorescent antibodies specific to glial fibrillary acidic protein (GFAP), which is a marker for astrocytes, and L1 cell adhesion molecule (L1CAM1), which is a marker for neurons.…”
Section: Resultsmentioning
confidence: 91%
“…Astrocytes are the most widespread glial cells. In the case of AD pathogenesis, which directly involves Aβ, they both internalize and degrade Aβ and prevent extracellular plaque aggregation [ 10 , 13 , 14 , 15 , 16 ]. Activated astrocytes have been shown to markedly overexpress S100B, also during AD [ 8 , 17 ], and most of these astrocytes overexpressing S100B are closely associated with diffuse or neuritic Aβ plaques, thus being regarded as playing a significant role in pathogenic processes [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, AST-Exos that are secreted under normal circumstances are recognized for their neurotrophic and neuroprotective benefits. Conversely, when astrocytes release Exos in adverse conditions, such as nutrient scarcity, oxidative stress, or inflammation, these exosomes can exert a protective effect on neurons, enhancing both neurite regeneration and growth [ 52 54 ]. Therefore, a large amount of AST-Exos isolated under normal physiological conditions is used in the treatment of neurotrauma.…”
Section: Neurologically Derived Exosomes For Neurotrauma Therapymentioning
confidence: 99%